Lingkungan Pembelajaran yang Produktif dan Kondusif - Nofri Hendri (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
One important factor that can maximize learning opportunities for children is the creation of a conducivelearning environment. Learning environment in this case, is everything related to where the learningprocess is carried out. While conducive means appropriate conditions and support the implementation ofthe learning process. The learning process is the interaction between the child and his environment, so thatin the child the information processing process occurs into knowledge, skills and attitudes as a result of thelearning process. There are several components that must be considered, as follows: understandingclassroom management, reasons, objectives and management strategies, design of the physicalenvironment of the classroom, creation of the environment, being a good communicator, dealing withproblematic behavior, class/school based programs, inhibiting factors and classroom managementprocedures considering these factors, it will be able to create a conducive and productive learningenvironment.